Using agent-based modelling to probe inclusive transport building design in practice. Issue 3 (10th June 2019) - Harding, John
Abstract : Subtle differences between universal design (UD) and inclusive design (ID) discourses impact inclusivity in practice. The level of service (LOS) is used as a proxy to evaluate inclusivity and agent-based modelling is used as a research instrument to probe how circulation and high levels of crowdedness impact inclusivity within a digital model of an underground transport building. Case 1 integrates 'first-generation' design methods and UD aims underpinned by social-model-of-disability discourses. Case 2 integrates 'next, next generation' design, vertical severance, service design and ID aims underpinned by socio-material-interactional discourses. While case 1 produced unsatisfactory results for inclusivity, case 2 increased the LOS and inclusivity throughout, and within the vertical circulation by five-fold, without increasing the overall cost or size of the building. Consequently, case 2 identifies how new ID guidelines, evaluation techniques and methods could enable inclusivity in practice.